VALUE BALANCE IN CONSUMER PROTECTION - Hasan, Dahsan (Journal of Humanity, 2015)
This research aims to describe how the realization of Balance in the Consumer Protection Act, describes how the responsibility of the parties (consumers, businessmen and the Government) so that it can realize the value of the balance in the protection of consumer, Research conducted in the framework of the preparation of this dissertation is to type the socio-juridical, in addition to researching the secondary legal materials in the form of legal regulations, manual and electronic law library, relevant research results in the field of law of particular problems in the field of consumer protection and other written materials, as well as researching various legal facts about consumer protection which occur in the field as well as its impact on the general public. The results showed that: 1) a form of value balance in consumer protection legislation lies in the synergy between the rights and obligations the rights and obligations of consumers, businessmen, as well as the duties and responsibilities of the Government, the supporters of both public institutions and private consumers are dispute resolution Efforts, and the use of contract oversight) of overall indicators are assessed if merged between the assessment of consumers and businessmen, as well as assessment of the Government then obtained 32 indicators of where the total number of indicators corresponding to the value of the balance of a total of 10 indicators, while the total number of which is not in accordance with the value of the balance as much as 21 indicators and only one indicator that his judgment balanced. So that the efforts made in the framework of the fulfilment of the rights and obligations of consumers and businessmen as well as maximize the task and responsibility of the Government is still having a lot of obstacles or not be able to realize the value of balance